Functional redundancy enhances microbial resilience in streams: mitigating flow perturbations - Lin, Qiaoyan; Zhang, Yixin; Marrs, Rob; Wu, Naicheng; Sekar, Raju; Juvigny-Khenafou, Noël; Matthaei, Christoph D.; Piggott, Jeremy (Frontiers in Microbiology, 2025)
Climate-change-induced and anthropogenic flow intermittency and habitat reduction threaten freshwater biodiversity and ecosystem functioning. Stream ecosystems are increasingly being evaluated for their capacity to endure climate change and anthropogenic disturbances. It remains uncertain how stream ecosystems can withstand multiple disturbances caused by habitat degradation and increasing flow intermittency. We conducted a mesocosm experiment in an ExStream system using benthic biofilm bacteria as a bioindicator to test microbial resilience to drying perturbations, followed by rewetting in streams of different habitats relative to continuous flow. The bacterial communities were compared in three types of habitat heterogeneity and two types of drying perturbation. We investigated how habitat heterogeneity influences bacterial community composition, microbial ecological networks, and ecosystem functioning under drying conditions and recovery after rewetting. The bacterial community composition shifted after drying events and flow resumption. Long-term drying led to decreased bacterial richness but increased bacterial diversity, measured by the Shannon index. Drying networks displayed greater complexity and vulnerability than control networks. These patterns were mitigated by flow resumption, resulting in comparable α-diversity and reduced microbial network complexity and vulnerability compared to the untreated controls. Long-term drying enabled bacterial survival by forming cysts but shifted microbial functions, with reduced xylan degraders, nitrogen fixers, ammonia oxidizers, and improved chitin degraders and atrazine metabolizers in diverse-heterogeneity habitats. Upon rewetting, microbes were rapidly activated and recolonized, and there was an increase in microbial metabolism processes, i.e., chitin degraders and aromatic hydrocarbon degraders. Despite variations in species composition across different stream habitats, hydrological connectivity and functionally analogous species supported by a complex microbial network contributed to the resilience and stability of benthic bacteria against environmental disturbances.